Human Rights of Dalits in Indian Perspective (International Journal of Food and Nutritional Sciences, 2022)
Human Rights are those rights which we get because of simply our existence as a human being in the world. Human Rights are provided to all human being regardless of their caste, class, gender, nationality, race or religion. According to ancient caste system Dalits fall outsides the caste system. Dalit as one of the depressed sections of our country face various challenges and discrimination in almost every sphere of Life from birth till death. They have given various human rights according to our Indian Constitution. Even though they have Human Rights, there are several instances of violation of their rights and they are combating for their Rights. This paper focuses on various constitutional fundamental rights for the Dalits, Directive Principles of State Policy concerning with them as well as various Acts for the upliftment of the Dalits. This paper is an endeavor to provide suggestions for the Dalits as well as for the various higher authorities and institutions which are working for the improvement of the circumstances of Dalits.